Comparison of real-time PCR and ELISA for the detection of crustacean shellfish allergens. Issue 4 (3rd April 2021) - Eischeid, Anne C.; Stadig, Sarah R.; Rallabhandi, Prasad
ABSTRACT: Food allergies are a significant public health concern, and crustacean shellfish represent one of the major FDA regulated food allergens. Allergic individuals must avoid foods containing crustaceans, and this necessitates highly sensitive and accurate detection methods. Two of the major methods used are protein-based ELISA and DNA-based real-time PCR. In order to properly compare these very different methodologies, we used identical split samples for a side-by-side comparison and analysed them using four different real-time PCR methods and two different commercial ELISA kits. Three real-time PCR assays targeting the mitochondrial 12S genes of shrimp, crab, and lobster were compared to a commercial ELISA assay for total crustacean protein. A fourth real-time PCR assay targeting the tropomyosin gene of shrimp was compared to an ELISA assay for shrimp tropomyosin. All comparisons were carried out in two different food matrices: Manhattan clam chowder and fish sauce. PCR assays had a more broad dynamic range (0.1–10 6 mg/kg) as compared to ELISA (200–4000 mg/kg) and did not show matrix interference like ELISA. In cases where the ELISA assays did not have matrix interference, there was good qualitative agreement between PCR and ELISA. Graphical Abstract: